Evidence for the Involvement of Fatty Acid Biosynthesis and Degradation in the Formation of Insect Sex Pheromone-Mimicking Chiloglottones in Sexually Deceptive Chiloglottis Orchids - Wong, Darren C. J.; Amarasinghe, Ranamalie; Pichersky, Eran; Peakall, Rod (Frontiers in Plant Science, 2018)
Hundreds of orchid species secure pollination by sexually luring specific male insects as pollinators by chemical and morphological mimicry. Yet, the biochemical pathways involved in the synthesis of the insect sex pheromone-mimicking volatiles in these sexually deceptive plants remain poorly understood. Here, we explore the biochemical pathways linked to the chemical mimicry of female sex pheromones (chiloglottones) employed by the Australian sexually deceptive Chiloglottis orchids to lure their male pollinator. By strategically exploiting the transcriptomes of chiloglottone 1-producing Chiloglottis trapeziformis at distinct floral tissues and at key floral developmental stages, we identified two key transcriptional trends linked to the stage- and tissue-dependent distribution profiles of chiloglottone in the flower: i) developmental upregulation of fatty acid biosynthesis and β-oxidation genes such as KETOACYL-ACP SYNTHASE, FATTY ACYL-ACP THIOESTERASE, and ACYL-COA OXIDASE during the transition from young to mature buds and flowers and ii) the tissue-specific induction of fatty acid pathway genes in the callus (the insectiform odour-producing structure on the labellum of the flower) compared to the labellum remains (non-odour-producing) regardless of development stage of the flower. Enzyme inhibition experiments targeting KETOACYL-ACP SYNTHASE activity alone in three chiloglottone-producing species (C. trapeziformis, C. valida, and C. aff. valida) significantly inhibited chiloglottone biosynthesis up to 88.4% compared to the controls. These findings highlight the role of coordinated (developmental stage- and tissue-dependent) fatty acid gene expression and enzyme activities for chiloglottone production in Chiloglottis orchids.